Shifting Narratives and Evolving Roles of Qatari Foreign Policy - Al-Etaibi, Abdulla Banndar. author. (orcid)0000-0003-4749-6448 Link aut Link
XV, 285 p. 6 illus.
Keywords: This book explores the strategic use of narratives by Qatari policymakers and how these narratives have driven significant shifts in Qatar’s foreign policy roles and directions. By examining Qatar’s foreign policy from 1995 to 2022, the book uses role theory and strategic narrative frameworks to provide a comprehensive analysis of Qatar’s unique foreign policy strategies, focusing on key turning points like the Arab Spring and crises that have shaped its identity on the global stage. Distinctively, the project offers an in-depth look at two main concepts—Kaabat al-Madhyum and Qatari Wahhabism—as central narratives in shaping Qatar’s foreign policy. By connecting these local, cultural frameworks to modern foreign policy strategies, it addresses a gap in the literature that often overlooks the influence of local traditions and values on state behaviour. The book leverages a thorough interpretive analysis of interviews, policy documents, and primary sources, making it valuable for readers interested in understanding how culture and identity intersect with foreign policy. The organisation of the book allows readers to understand Qatar’s foreign policy evolution through structured chapters that address the theoretical foundation, the impact of tribal heritage and values, Qatar’s response to regional crises, and its shifting narratives during events like the Arab Spring. This book meets the need for a nuanced analysis of a small state’s foreign policy influenced by traditional and modern narratives, providing insights valuable for students, researchers, and policymakers studying Middle Eastern politics and international relations. Dr. Abdulla Banndar Al-Etaibi is an Assistant Professor in the Department of International Affairs at Qatar University’s College of Arts and Sciences. He holds a PhD in International Relations from the Australian National University, an MSc in International Public Policy from University College London, and a BA in International Affairs from Qatar University. His research focuses on the intersection of narratives, identity, and foreign policy, with a particular emphasis on the Gulf region. He has written extensively on small-state diplomacy, mediation, role theory, and hybrid diplomacy, examining how states merge traditional authority with modern statecraft to navigate regional and global politics.